HUBUNGAN ANTARA POLA ASUH DEMOKRATIS DENGAN DISIPLIN BELAJAR PADA SISWA DI SMA NEGERI 1 LABUAPI - Khairiyaturrizkyah Khairiyaturrizkyah; Nuraeni Nuraeni (Universitas Pendidikan Mandalika, 2018)
Democratic parenting is the ordinance of parents treating children, decisions are taken with mutual consent, Discipline learning is the attitude of students that includes good study preparation. The purpose of research is to know the relationship Between Democratic Parenting With Discipline Learning In Students Class X in SMAN 1 Labuapi West Lombok Regency Lesson Year 2017/2018. The sampling technique used Proportional Random Sampling the number of samples in this study as many as 30 students taken 25% of the total students (population) of 121 Students. In this research, data collection method used questionnaire as main method and method of documentation, observation, interview as complement method. Data analysis used is statistical analysis with Product Moment Correlation formula. Based on the calculation of rxy value obtained in this study is 0.475, while the rxy value in the table with a significant level of 5% and N = 30 is 0.361 or (0.475> 0.361), this fact indicates that the rxy value obtained in this study is greater than the rxy value of the table. Then it can be argued that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So the conclusions of the analysis in this study is to show there is a Relationship Between Democratic Parenting With Discipline Learning In Students Class X in SMAN 1 Labuapi West Lombok Regency Lesson Year 2017/2018. That means the results of this study are